Reporting vybrané firmy - Procházková, Kristýna (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Předkládaná bakalářská práce se zabývá problematikou zavádění reportingu. Z provedených analýz vyplynulo, že reporting výroby nemá. Potřebuje jej pro zavedení a vytvoření podmínek pro získávání informací. Proto součástí mé práce jsou návrhy na vytvoření podmínek reportu pro zavedení efektivního reportingu, který by složil k řízení nákladů.

The present bachelor thesis deals with the theme of introducing the reporting. The performed analyzes showed that the company has no production reporting. It needs it in order to introduce and to create the conditions for obtaining of information. Therefore, my thesis includes the proposals for creating the conditions for report, so that an effective reporting can be launched and serve for costs management.
Reporting of the Selected Company
Keywords: Controlling; Reporting; Vnitropodnikové účetnictví; Náklady; Kalkulace; kalkulační vzorec; Controlling; Reporting; Internal accounting; costs; calculation; calculation formula